Perceptions and evaluations of the implementation of the therapeutic community model in youth orientation centers in Costa Rica - Masís Méndez, María José (2023)
Introduction: It starts from critical criminology and criminal legal sociology as epistemic positions to understand how the creation, implementation, and subsequent weakening of the therapeutic community model in youth facilities in Costa Rica. Objective: Specifically, some potentialities and limitations of the implementation of the therapeutic community model and psychological practice are analyzed in accordance with the Organic Law of the Jurisdiction of Minors (LOJTM) and the Juvenile Criminal Justice Law (LJPJ). Method: The qualitative methodological perspective feeds this research and the analysis material is based on semi-structured interviews with key informants (psychology professionals) and documentary review. Results: From the analysis it emerges that the therapeutic community model was implemented in a differentiated way in youth centers. Its implementation was weakened due to social, political and economic changes that began in the eighties and in the following years, which had a negative impact on the work carried out with juvenile offenders. In addition, when contrasting the psychological work within the framework of the LOJTM and the LJPJ, the complex relationship that has prevailed between the legal and psychosocial criteria in these venues is evident. [Continue reading in the article]